Goodnight, Tiptoe - Dunbar, Polly (Walker London, 2010)
"I'm not sleepy", says Tiptoe, while Tilly gives him his goodnight kiss. Boom! Boom! Boom! goes Tiptoe's crum, while Tilly sings him a goodnight lullaby. Will a bedtime story do the trick and send Tiptoe off to sleep?